2014
DOI: 10.3389/fsurg.2014.00025
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Donor Motivations in Living Donor Liver Transplantation

Abstract: Objectives: The introduction of the living donor liver transplantation (LDLT) in Egypt as in elsewhere, has raised important psychological conflicts and ethical questions. The objective of this study was to get better understanding of the potential donors’ motives toward LDLT.Methods: This study was conducted on consecutive 193 living-liver donors who underwent partial hepatectomy as donors for LDLT during the period between April 2003 and January 2013, at the National Liver Institute Menoufeyia University, Eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Familial relationship between donor and recipient strongly influences the level of donor’s motivation, especially in Asian cultures [1]. Family background or dynamics may also play a significant role in the donor’s decision-making process [10]. In addition, the suggestion or expectation of the recipient or family, even if not through coercion, may affect the donor’s decision-making, although this is uncommon [11].…”
Section: Introductionmentioning
confidence: 99%
“…Familial relationship between donor and recipient strongly influences the level of donor’s motivation, especially in Asian cultures [1]. Family background or dynamics may also play a significant role in the donor’s decision-making process [10]. In addition, the suggestion or expectation of the recipient or family, even if not through coercion, may affect the donor’s decision-making, although this is uncommon [11].…”
Section: Introductionmentioning
confidence: 99%
“…Liver transplantation (LT) is the principal treatment for end‐stage liver diseases and selected cases of liver neoplasms . Living donor liver transplantation (LDLT) either supplements liver transplantation from deceased donors by increasing the donor pool or serves as a sole source of liver graft in some countries that do not allow donation from deceased donors for cultural, social, or religious reasons . Postreperfusion syndrome (PRS) and ischemia reperfusion injury (IR) are well‐known complications in LT with a major impact on graft and patient outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…10 A study from Egypt aiming to analyze donor motivations in living-donor liver transplant has shown that all donors had expressed the importance of their religious beliefs in their decision. 11 Some Muslim scholars claim that living-donor organ transplant, extraction of organs from dead individuals, and transplant are prohibited. 12 However, Sheikh Hassanein Makhlouf, the Grand Mufti of Egypt, allowed corneal grafting in 1952.…”
Section: Organ Donation In Muslim Countriesmentioning
confidence: 99%